Transparency and credibility: Monetary policy with unobservable goals - Jon Fausty; Lars E. O. Svensson (Sveriges Riksbank, 1998)
We define and study transparency, credibility, and reputation in a model where the central bank's characteristics are unobservable to the private sector and are inferred from the policy outcome. A low-credibility bank optimally conducts a more expansionary policy than a high-credibility bank, in the sense that it induces higher inflation, but a less expansionary policy in the sense that it induces lower inflation and employment than expected. Increased transparency makes the bank's reputation and credibility more sensitive to its actions. This has a moderating influence on the bank's policy, and induces the bank to follow a policy closer to the socially optimal one. Full transparency of the central bank's intentions is generally socially beneficial, but frequently not in the interest of the bank. Somewhat paradoxically, direct observability of idiosyncratic central bank goals removes the moderating incentive on the bank and leads to the worst equilibrium.
Keywords: E52; E58; 330